Impact of Digital Tooth Preparation Evaluation Technology on Preclinical Dental Students' Technical and Self‐Evaluation Skills. Issue 1 (1st January 2016) - Gratton, David G.; Kwon, So Ran; Blanchette, Derek; Aquilino, Steven A.
Abstract : The aim of this study was to evaluate the effect of digital tooth preparation imaging and evaluation technology on dental students' technical abilities, self‐evaluation skills, and the assessment of their simulated clinical work. A total of 80 second‐year students at one U.S. dental school were assigned to one of three groups: control (n=40), E4D Compare (n=20), and Sirona prepCheck (n=20). Students in the control group were taught by traditional teaching methodologies, and the technology‐assisted groups received both traditional training and supplementary feedback from the corresponding digital system. Three outcomes were measured: faculty technical score, self‐evaluation score, and E4D Compare scores at 0.30 mm tolerance. Correlations were determined between the groups' scores from visual assessment and self‐evaluation and between the visual assessment and digital scores. The results showed that the visual assessment and self‐evaluation scores did not differ among groups (p>0.05). Overall, correlations between visual and digital assessment scores were modest though statistically significant (5% level of significance). These results suggest that the use of digital tooth preparation evaluation technology did not impact the students' prosthodontic technical and self‐evaluation skills. Visual scores given by faculty and digital assessment scores correlated moderately in only two instances.